The unlikely adventures of Mabel Jones - Mabbitt, Will (Mabbitt, Will. Mabel Jones, 2015)
"Mabel Jones finds herself aboard the Feroshus Maggot--a ship crewed by the strangest bunch of pirates you'd (never) want to meet. She then has to find pieces of an X-shaped puzzle that in her hands could be her ticket home, but in the hands of Captain Split, they'd give him the power to assemble a pirate militia to take over London!"--